Generation of HLA Universal Megakaryocytes and Platelets by Genetic Engineering - Figueiredo, Constanca; Blasczyk, Rainer (Frontiers in Immunology, 2021)
Patelet transfusion refractoriness remains a relevant hurdle in the treatment of severe alloimmunized thrombocytopenic patients. Antibodies specific for the human leukocyte antigens (HLA) class I are considered the major immunological cause for PLT transfusion refractoriness. Due to the insufficient availability of HLA-matched PLTs, the development of new technologies is highly desirable to provide an adequate management of thrombocytopenia in immunized patients. Blood pharming is a promising strategy not only to generate an alternative to donor blood products, but it may offer the possibility to optimize the therapeutic effect of the produced blood cells by genetic modification. Recently, enormous technical advances in the field of in vitro production of megakaryocytes (MKs) and PLTs have been achieved by combining progresses made at different levels including identification of suitable cell sources, cell pharming technologies, bioreactors and application of genetic engineering tools. In particular, use of RNA interference, TALEN and CRISPR/Cas9 nucleases or nickases has allowed for the generation of HLA universal PLTs with the potential to survive under refractoriness conditions. Genetically engineered HLA-silenced MKs and PLTs were shown to be functional and to have the capability to survive cell- and antibody-mediated cytotoxicity using in vitro and in vivo models. This review is focused on the methods to generate in vitro genetically engineered MKs and PLTs with the capacity to evade allogeneic immune responses.